Frog rescue : changing the future for endangered wildlife - Hamilton, Garry, 1962- (Buffalo, N.Y. : Firefly Books (U.S.), 2004)
Introduces readers to frogs and their habitats, explains the threats they face, and explores efforts to protect them.
Includes index.
Book Links (A.L.A.)
School Library Journal
Wilson's Junior High School
8.9
5-8
Keywords: Endangered species -- Juvenile literature; Frogs -- Juvenile literature; Wildlife conservation -- Juvenile literature; Endangered species; Frogs; Wildlife conservation; Endangered species; Frogs; Wildlife conservation